Bilateral Unusual Variant of Sternalis Muscle. - Simmi M,; Dalpat SC,; Tuhin G, (Department of Surgery, UKM Medical Centre, 2012)
There is a need to record and discuss unusual anatomical variants with the advent of complex diagnostic and therapeutic tools as these variants could present a challenge to the radiologist or surgeon in arriving at a diagnosis. The sternalis muscle has been widely reviewed and studied since 17th century. It can be easily overlooked during breast surgery and may often cause diagnostic dilemma on mammography or CT scans. We hereby, report an unusual bilateral sternalis along with bilateral variations in pectoralis major muscles. Although sternalis has no known functional role, its presence has surgical implications during breast implant reconstruction surgery and in radiation therapy in breast carcinoma cases.